Seropositive pigs to Toxoplasma gondii (Apicomplexa: Toxoplasmatinae) sent to slaughter and destined for human consumption - de Almeida, Wanderley M.; Miranda, Zander B.; Flausino, Walter; Coelho, Cleide D.; Fonseca, Ana Beatriz M.; Lopes, Carlos Wilson G. (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. de Almdeida W., Miranda Z.B., Flausino W., Coelho C.D., Fonseca A.B.M. & Lopes C.W.G. [Seropositive pigs to Toxoplasma gondii (Apicomplexa: Toxoplasmatinae) sent to slaughter and destined for human consumption.] Suínos sororreagentes a Toxoplasma gondii (Apicomplexa: Toxoplasmatinae) enviados para abate e destinados ao consumo humano. Revista Brasileira de Medicina Veterinária, 37(4):397-400, 2015. Curso de Pós-Graduação em Medicina Veterinária - Higiene Veterinária e Processamento Tecnológico de Produtos de Origem Animal, Faculdade de Veterinária, Universidade Federal Fluminense, Rua Vital Brasil Filho, 64, Vital Brazil, Niterói, RJ 24230-340, Brasil. E-mail: wanderleyma@yahoo.com.br This study aimed to determine the frequency of pigs seropositive to Toxoplasma gondii by indirect immunofluorescence assay with cutoff 1:16. Of blood samples collected at slaughter, 250 of them were from animals raised in the State of Minas Gerais; while 181 were from the State of Rio de Janeiro with a total of 431 examined samples. Of these, 19/250 (4.41%) of MG and 39/181 (9.04%) of RJ, determining a total of 13.45% seropositive animals. Regardless of slaughter be under the control of the inspection service, the precedence of the animals was highly significant (p = 0.0001) in the number of seropositive animals. Although the percentage of seropositive animals to T. gondii from both regions studied in this work, and from the point of view of a public health problem, pork and its frescal type products may continue to be considered as a source of infection of this coccidia for humans, if they are consumed as raw or undercooked.